2013
DOI: 10.1289/ehp.1206039
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Intracellular Redox Changes in Ozone-Exposed Airway Epithelial Cells

Abstract: Background: The toxicity of many xenobiotic compounds is believed to involve oxidative injury to cells. Direct assessment of mechanistic events involved in xenobiotic-induced oxidative stress is not easily achievable. Development of genetically encoded probes designed for monitoring intracellular redox changes represents a methodological advance with potential applications in toxicological studies.Objective: We tested the utility of redox-sensitive green fluorescent protein (roGFP)–based redox sensors for moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Glutaredoxin 1 (Grx1) is a thiol oxidoreductase that selectively interacts with GSH31. In previous reports, a Grx1-roGFP2 fusion protein was constructed to monitor the dynamics of reduced GSH versus oxidized GSH (GSSG)323334. We therefore constructed an EGFP-Grx1-NPM1 fusion protein and observed its translocation dynamics in a live-cell imaging system.…”
Section: Resultsmentioning
confidence: 99%
“…Glutaredoxin 1 (Grx1) is a thiol oxidoreductase that selectively interacts with GSH31. In previous reports, a Grx1-roGFP2 fusion protein was constructed to monitor the dynamics of reduced GSH versus oxidized GSH (GSSG)323334. We therefore constructed an EGFP-Grx1-NPM1 fusion protein and observed its translocation dynamics in a live-cell imaging system.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, we may consider the case of a hypothetical dithiocarbamate derivative that inhibits Grx, the proximal enzyme in the relay through which roGFP senses the oxidant effect of H 2 O 2 on E GSH (Fig. 1, [101,212]). Since the effect of Grx inhibition would be to sever the ability of roGFP to sense E GSH , any oxidant effect that this dithiocarbamate derivative may have on E GSH, either through the production of H 2 O 2 or by direct reactivity with GSH, could not be reported by the sensor, resulting in a false negative result.…”
Section: Specific Challenges Using Oxidant Stress Sensors In Redomentioning
confidence: 99%
“…1). Our laboratory used this approach in a recent study [212] that investigated the basis for roGFP2-reported increases in E GSH induced in human airway epithelial cells undergoing real time exposure to O 3 , a highly reactive environmental electrophile. The requirement for Grx in the O 3 -induced E GSH change was tested two different ways.…”
Section: Specific Challenges Using Oxidant Stress Sensors In Redomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the dependence of Zn 2+ -induced responses on H 2 O 2 , the present study expanded our previous live-cell imaging approach to monitor oxidative changes in the cytosol and mitochondria of HAEC exposed to Zn 2+ [28] , [29] . We utilized cytosolic overexpression or ectopic mitochondrial expression of the H 2 O 2 scavenging enzyme catalase in BEAS-2B cells bearing the genetically-encoded fluorogenic ratiometric sensors HyPer or roGFP2, which report on H 2 O 2 and the glutathione redox potential ( E GSH ), respectively [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%